1909 Iowa Acts 258 - (:unkn) unknown (My University, 1909)
Ordinances Legalized, § 1, Ordinance No. 29: Legalized ordinances in the town of Callender due the mayor not being a U.S. citizen. Ordinance 29 prohibited the discharge of missiles from air guns and other weapons in the corporate limits of Callender.
Keywords: DISCHARGE